Regu larities of the of simultaneous discharge of ions. Theory of electrochemical synthesis - Pototskaya, V. V.; Gichan, O. I.; Omelchuk А. О. (Reports of the National Academy of Sciences of Ukraine, 2021)
The mechanisms of simultaneous discharge of two ions for different conditions of electrode polarization [concentration polarization, mixed (concentration-kinetics) polarization, and kinetic control in the case of delayed discharge of both ions] are shown. We show how the independent processes of discharge of ions become dependent at the simultaneous discharge. The equation of polarization curve for the electrochemical synthesis in the case of concentration polarization of the electrode is derived (we consider the simultaneous discharge of two ions and the proceeding delayed heterogeneous chemical reaction of synthesis). The overvoltage shift depends on the charge of ions discharged, density of discharge currents, density of exchange current of the chemical reaction of synthesis, and difference in the standard potentials.